Fluoride concentration in dentine as a biomarker of fluoride intake in European roe deer (Capreolus capreolus) - an electron-microprobe study - Richter, Heiko; Kierdorf, Uwe; Richards, Alan; Melcher, Frank; Kierdorf, Horst (Archives of oral biology, 2011)
OBJECTIVE: Fluoride concentration in dentine has been recommended as the best marker for the level of chronic fluoride intake and the most suitable indicator of an individual's total body burden of fluoride. We analysed fluoride concentrations in the dentine of cheek teeth of European roe deer from fluoride-polluted habitats to retrospectively assess the level of fluoride uptake into the tissue. Thereby, we tested the hypothesis of the existence of mechanisms that limit fluoride intake of individuals and fluoride exposure of forming dental hard tissues during the late foetal and early postnatal periods in the species. DESIGN: Using electron-microprobe analysis, fluoride profiles were obtained on sectioned P(4)s, M(1)s, and M(3)s from individuals exhibiting pronounced dental fluorosis. Fluoride concentrations were compared between early formed (peripheral) and late-formed (juxtapulpal) dentine both within single teeth and amongst the three different teeth studied. RESULTS: Peripheral dentine of the M(1), which is formed during the late foetal and early postnatal periods, exhibited markedly lower fluoride concentrations than juxtapulpal dentine of the same tooth and both, peripheral and juxtapulpal dentine of P(4) and M(3) that are formed post-weaning. CONCLUSIONS: Our study provides strong support for the hypothesis that in the European roe deer the prenatal and early postnatal (pre-weaning) stages of dental development are (largely) protected against exposure to excess fluoride. This is attributed to the operation of certain protective mechanisms during these periods.
Keywords: dentin; Environmental Pollutants; látky znečišťující životní prostředí; Tissue Distribution; Dentin; vystavení vlivu životního prostředí; Molar; Male; Retrospective Studies; mikroanalýza elektronovou sondou; Česká republika; vápník; mužské pohlaví; Body Burden; odontogeneze; vysoká zvěř; Environmental Exposure; Fluorosis, Dental; Czech Republic; moláry; obsah radioaktivních látek v organizmu; Calcium; Electron Probe Microanalysis; Mandible; zvířata; dentální fluoróza; retrospektivní studie; tkáňová distribuce; Fluorides; biologické markery; premolár; Deer; mandibula; zubní sklovina; Dental Enamel; Biomarkers; Odontogenesis; fluoridy; Bicuspid; Animals